A ação cardiovascular dos peptídeos ricos em prolina da Bothrops jararaca não está relacionada com a inibição da enzima conversora de angiotensina I e potenciação da Bradicinina - Ianzer, Danielle Alves [UNIFESP] (2006)
In the present study, were evaluated the cardiovascular effects of four Bradykinin Potentiating Peptides (BPPs) in spontaneously hypertensive rats (SHR). The peptides were selected from a family of 19 proline-rich oligopeptides found either in the venom of Bothrops jararaca or derived from the C-type natriuretic peptide precursor of the B. jararaca brain. These peptides were chosen for their distinct features concerning the in vitro and in vivo inhibition of the somatic angiotensin converting enzyme (ACE), and the ex-vivo and in vivo potentiation of bradykinin (BK). The experiments were performed in conscious adult male hypertensive rats (SHR) and normotensive rats (WT), with polyethylene catheters implanted into the femoral artery for the mean arterial pressure (MAP) and heart rate (HR) measurements, and into the femoral vein for drug administration. The MAP and HR were monitored for 6 hours after the intravenous injection of BPPs. All four BPPs showed potent cardiovascular effects in the range between 0.47 nmol/Kg and 710 nmol/Kg. The anti-hypertensive effect of BPPs was biphasic, presenting an initial reduction of MAP in the first 20 minutes after the peptide injection (acute period), folowing by other fall in 60-80 minutes after BPP and maintained for even of 6 hours (late period). The maximal change on MAP was observed using the BPP-10c at a dose of 71 nmol/Kg (-53 ± 6 mmHg). Differently from the other three BPPs, the BPP-7a presented a weak in vitro inhibition of the somatic ACE [Ki(app) ≅ 50 μM], and was unable to potentiate the BK, even at concentrations 100-fold higher than the concentrations used for the other peptides. However, the BPP-7a at a dose of 14.2 nmol/Kg caused the maximum MAP fall of the -45 ± 6 mmHg in SHR. In contrast, was showed that during the BPP antihypertensive effect in SHR there were not alteration of the BK hypotensive and the Ang I pressure responses, during both acute and late periods. These results indicate the participation non elucidated of mechanisms in the cardiovascular effects caused by these peptides. The action mediated by an orphan receptor has not been discarded. These characteristics open new perspectives for the use of BPPs as anti-hypertensive drugs.